An Analysis of Presuppositions in the Selected Song Lyrics of Hendry Moodie’s Album - Simanjuntak, Fransisca; Hasibuan, Wan Syahfina Yahmi; Manurung, Lastri W; Manik, Sondang (English Lecturers and Teachers Association (ELTA), 2025)
This study analyzed the presuppositions in the song lyrics of Hendry Moodie’s album to uncover deeper meanings and emotional nuances in his music. The research focused on five selected songs: